Analyse der Bewegungstechnik des Weitsprungs anhand zeitdiskreter und zeitkontinuierlicher Daten - Jaitner, T. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
Long jump trials of specialist long jumpers, decathlete and sports students were filmed two-dimensional with one high speed camera. Performance during Take-Off (TO) was analyzed based on time continuous. All trails were compared for similarity and classified by cluster analysis (Schöllhorn 1999). Additional cluster analyses considered time discrete variables only. Cluster analysis separated for both data sets groups of long jump trials but no classification according to jumping length was found. The results indicate that different TO strategies may result in comparable jumping length. Consequences on the analysis and diagnosis of sports techniques are discussed.